Lärarutbildningen som demokratiskt rum – medvetet engagemang och erbjudanden om ömsesidighet - Knutes Nyqvist, Helen; Holmberg, Kristina (Utbildning & Lärande, 2023)
Education is the cornerstone for developing a democratic society, and vital to the work of fostering new generations of citizens. Therefore, knowledge about how to work with democracy in school and in teacher training is important. Education is often considered as the arena where society can transfer democratic values and give people insights into the meaning of democracy. However, there is a lack of empirical research conducted in classrooms, which urges us to investigate the interpretation of how the doing of democracy in education is carried out. In this case study we explore how democratic values are or are not, manifested by teacher students and teachers in teacher education. In order to understand democracy in education, we ask questions about student influence, reciprocity and critical thinking. The empirical material consists of observations and narratives of teacher students, and the analysis is done by using Cultural analysis. The findings show that teacher educators’ and teacher students’ engagement, and mutual responsibility, is significant for democratic education. Also, critical aspects are identified concerning students' expectations, teachers' limited space for action and an inflexible organizational structure. To conclude, we have revealed a need for more research, to continue the debate of democracy in teacher education.